Cerebral hemodynamic responses to seizure in the mouse brain: simultaneous near-infrared spectroscopy-electroencephalography study - Lee, Seungduk; Lee, Mina; Koh, Dalkwon; Kim, Beop-Min; Choi, Jee Hyun (SPIE-SOC PHOTO-OPTICAL INSTRUMENTATION ENGINEERS, 2010)
We applied near-infrared spectroscopy (NIRS) and electroencephalography (EEG) simultaneously on the mouse brain and investigated the hemodynamic response to epileptic episodes under pharmacologically driven seizure. gamma-butyrolactone (GBL) and 4-aminopyridine (4-AP) were applied to induce absence and tonic-clonic seizures, respectively. The epileptic episodes were identified from the single-channel EEG, and the corresponding hemodynamic changes in different regions of the brain were characterized by multichannel frequency-domain NIRS. Our results are the following: (i) the oxyhemoglobin level increases in the case of GBL-treated mice but not 4-AP-treated mice compared to the predrug state; (ii) the dominant response to each absence seizure is a decrease in deoxyhemolobin; (iii) the phase shift between oxy- and deoxyhemoglobin reduces in GBL-treated mice but no 4-AP-treated mice; and (iv) the spatial correlation of hemodynamics increased significantly in 4-AP-treated mice but not in GBL-treated mice. Our results shows that spatiotemporal tracking of cerebral hemodynamics using NIRS can be successfully applied to the mouse brain in conjunction with electrophysiological recording, which will support the study of molecular, cellular, and network origin of neurovascular coupling in vivo. (C) 2010 Society of Photo-Optical Instrumentation Engineers. [DOI:10.1117/1.3365952]
Keywords: ABSENCE SEIZURES; BLOOD-VOLUME; EEG-FMRI; HEMOGLOBIN; EPILEPSY; OXYGENATION; TOPOGRAPHY; PARAMETERS; FREQUENCY; CORTEX